PENGARUH MODEL PEMBELAJARAN DAN KEMANDIRIAN BELAJAR TERHADAP PEMAHAMAMAN KONSEP BIOLOGI - MELLI YUNERTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
The purpose of this study is to determine the influence of learning models and learning independence on the understanding of the concept of Biology of grade XI high school students in the city of South Tangerang. The affordable population in this study is students of SMAN 4 South Tangerang City and SMAN 8 South Tangerang City class XI science for the 2017/2018 academic year totaling 160 students. The research method used is experimental, sampling technique using random sampling. The research design used is a 2 X 2 factorial design with three variables consisting of two independent variables, namely learning models and learning independence and one dependent variable, namely concept understanding. The data collection process is carried out by questionnaires and written tests. The collected data was analyzed using the two-track ANOVA technique, The results showed that (1) There was a significant influence of the learning model on the Understanding of Biology Concepts of State High School students in South Tangerang City. This is evidenced by the acquisition of Sig. = 0.000 < 0.05 and Fh = 26.537. (2) There is a significant influence of learning independence on the Understanding of Biology Concepts of State High School students in South Tangerang City. This is evidenced by the acquisition of Sig. = 0.000 < 0.05 and Fh = 39.743. (3) There is a significant interaction influence of learning models and types of learning interests on the Understanding of Biology Concepts of State High School students in South Tangerang City. This is evidenced by the acquisition of Sig. = 0.015 < 0.05 and Fh = 6.178. Based on the results of the study, the need for the right learning model in learning activities and high learning independence to improve the understanding of Biology concepts in students at SMAN in South Tangerang. ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui pengaruh model pembelajaran dan kemandirian belajar terhadap pemahaman konsep Biologi siswa kelas XI SMAN di kota Tangerang Selatan. Populasi terjangkau dalam penelitian ini adalah siswa SMAN 4 Kota Tangerang Selatan dan SMAN 8 Kota Tangerang Selatan kelas XI IPA tahun pelajaran 2017/2018 yang berjumlah 160 siswa. Metode penelitian yang digunakan adalah eksperimen, teknik pengambilan sampel menggunakan random sampling. Rancangan penelitian yang yang digunakan adalah desain factorial 2 X 2 dengan tiga variabel yang terdiri dua variabel bebas yaitu model pembelajaran dan kemandirian belajar dan satu variabel terikat yaitu pemahaman konsep. Proses pengumpulan data dilaksanakan dengan angket dan tes tertulis. Data yang terkumpul dianalisis menggunakan teknik ANOVA dua jalur, Hasil penelitian menunjukan bahwa (1) Terdapat pengaruh yang signifikan model pembelajaran terhadap Pemahaman Konsep Biologi siswa SMA Negeri di Kota Tangerang Selatan. Hal ini dibuktikan dengan perolehan Sig. = 0,000 < 0,05 dan Fh = 26,537. (2)Terdapat pengaruh yang signifikan kemandirian belajar terhadap Pemahaman Konsep Biologi siswa SMA Negeri di Kota Tangerang Selatan. Hal ini dibuktikan dengan perolehan Sig. = 0,000 < 0,05 dan Fh = 39,743. (3) Terdapat pengaruh interaksi yang signifikan model pembelajaran dan jenis minat belajar terhadap Pemahaman Konsep Biologi siswa SMA Negeri di Kota Tangerang Selatan. Hal ini dibuktikan dengan perolehan Sig. = 0,015 < 0,05 dan Fh = 6,178. Berdasarkan hasil penelitian perlunya model pembelajaran yang tepat dalam kegiatan belajar serta kemandirian belajar yang tinggi untuk meningkatkan pemahaman konsep Biologi pada siswa di SMAN di Tangerang Selatan.